Hypnozoite depletion in successive Plasmodium vivax relapses. - Rintis Noviyanti; Kelly Carey-Ewend; Leily Trianty; Christian Parobek; Agatha Mia Puspitasari; Sujata Balasubramanian; Zackary Park; Nicholas Hathaway; Retno A S Utami; Saraswati Soebianto; Jeny Jeny; Frilasita Yudhaputri; et al. (Public Library of Science (PLoS), 2022)
Genotyping Plasmodium vivax relapses can provide insights into hypnozoite biology. We performed targeted amplicon sequencing of 127 relapses occurring in Indonesian soldiers returning to malaria-free Java after yearlong deployment in malarious Eastern Indonesia. Hepatic carriage of multiple hypnozoite clones was evident in three-quarters of soldiers with two successive relapses, yet the majority of relapse episodes only displayed one clonal population. The number of clones detected in relapse episodes decreased over time and through successive relapses, especially in individuals who received hypnozoiticidal therapy. Interrogating the multiplicity of infection in this P. vivax relapse cohort reveals evidence of independent activation and slow depletion of hypnozoites over many months by multiple possible mechanisms, including parasite senescence and host immunity.